Civil cases involving foreign individuals: Specificities and issues - Aliya Muidenova; Zhauhar Kozhantaeva; Aitugan Abdizhami; Akzada Madaliyeva; Akmanat Zhuldybayeva (Khazanah Hukum, 2025)
This research is relevant due to the lack of an effectively functioning institute of foreign individuals’ representation on the territory of the Republic of Kazakhstan. The work aims to analyse legislative regulations on foreign persons’ legal status in civil proceedings, their rights and obligations on the territory of Kazakhstan. The work analysed the status of non-resident individuals in accordance with the valid Civil Procedure Code of the Republic of Kazakhstan. It was found that there are problematic aspects in the current legislation regarding the functioning of an institute of foreign persons’ representation. According to the above, the main directions for improving the provisions of the Civil Procedure Code of the Republic of Kazakhstan for resolving this conflict have been provided in the work. The practical value of the obtained results is to increase the efficiency of the national legal system and to provide greater guarantees for foreign citizens.